2022
DOI: 10.1002/celc.202101675
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of Ultrathin NiO Nanosheet‐Arrays on MOF‐Derived Porous Co3O4 Scaffolds as High‐Performance Cathode for Asymmetric Supercapacitors

Abstract: The ever‐increasing market for portable and wearable electronic devices creates a demand for high‐efficiency electrochemical energy storage devices with excellent flexibility. Herein, MOF‐derived porous Co3O4 scaffolds as the core, ultrathin NiO nanosheet‐arrays as the shell, well‐aligned core‐shell structured Co3O4@NiO were constructed on carbon cloth (CC/Co3O4@NiO) via facile chemical bath methods. Composition, morphological structure, and electrochemical performance of the hybrid nanomaterials were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…These two values were greater than 0.5, indicating diffusion and capacitive-controlled electrochemical processes (Figure S4b). The capacitive and diffusive-controlled contributions were estimated by the following equation i v = k 1 v + k 2 v 1 / 2 where k 1 v is the surface-controlled current, k 2 v 1/2 is the diffusion-controlled current, and i v is the total current response of the CV curves. The linearly fitted slope of i / v 1/2 vs v 1/2 was used to calculate the k 1 and k 2 values.…”
Section: Resultsmentioning
confidence: 99%
“…These two values were greater than 0.5, indicating diffusion and capacitive-controlled electrochemical processes (Figure S4b). The capacitive and diffusive-controlled contributions were estimated by the following equation i v = k 1 v + k 2 v 1 / 2 where k 1 v is the surface-controlled current, k 2 v 1/2 is the diffusion-controlled current, and i v is the total current response of the CV curves. The linearly fitted slope of i / v 1/2 vs v 1/2 was used to calculate the k 1 and k 2 values.…”
Section: Resultsmentioning
confidence: 99%
“…Most researchers choose NH 3 ·H 2 O as a complexant regent to control the deposition rate in the preparation of NiO films. 43,58,132 Boo et al explored the effect of NH 3 ·H 2 O addition on the morphology and EC properties of NiO films deposited by CBD. They found that adding an appropriate amount of NH 3 ·H 2 O is important for achieving a balanced EC performance between Δ T and cyclic durability.…”
Section: Preparation Methods Of Nio-based Ec Filmsmentioning
confidence: 99%
“…Due to the chemical reaction controlling the CBD process, it is generally necessary to add additives to the deposition solution to control the deposition rate and obtain a uniform film. Most researchers choose NH 3 ÁH 2 O as a complexant regent to control the deposition rate in the preparation of NiO films 43,58,132. Boo et al explored the effect of NH 3 ÁH 2 O addition on the morphology and EC properties of NiO films deposited by CBD.…”
mentioning
confidence: 99%
“…27–32 However, the poor electrical conductivity and low utilization rate of NiO limit its application in the field of high-performance supercapacitors. 33–35…”
Section: Introductionmentioning
confidence: 99%